Ecological Upgrade of Normal-Strength Mortars by Using High Volume of GGBS - Peiyuan Chen; Shicheng He; Pengju Wang; Ying Xu; Xiuping Hu; Qian Chen (Advances in Civil Engineering)
Normal-strength concrete is widely used in construction sites considering the cost, technology, and structural safety. The ecological upgrade of such materials is more meaningful for the sustainable development in a greener way. To this end, the feasibility of ecological upgrade of normal-strength mortars (NSM) by using high volume of ground granulated blast furnace slag (GGBS) (70%–90%) was evaluated in this paper. Comprehensive experiments were conducted to investigate the influences of experimental variables such as content of cement, curing temperature, and mass ratio of water to binder (w/b) on the fresh properties, compressive strength, hydration products, microstructure, and pore structure of NSM. Ecoefficiency evaluation was conducted based on the energy requirement for the whole production of cement and GGBS. Experimental results showed that ecological upgrade of NSM was viable and feasible. When substituting 70% to 90% cement by GGBS, the energy requirement of 1 t binder can be accordingly saved by 67% to 86%, and the performance energy can be reduced from 25.4 (kWh/t)/MPa to 6 to 8 (kWh/t)/MPa. With proper contents of GGBS (70% or 75%), the 28 d compressive strengths were acceptable with reductions less than 10%. Evaluated curing temperatures and decreased w/b were viable methods to promote the early-age compressive strength of NSM incorporating high volume of GGBS. For instance, raising the curing temperature to 40°C can help achieve higher early-age compressive strength than that of the control group. In addition, the pore sizes within ZII (<100 nm) of GGBS-incorporated NSM were refined by over 20 nm.